Characteristics and long-term ablation outcomes of supraventricular arrhythmias in hypertrophic cardiomyopathy: a 10-year, single-center experience. (14th October 2021) - Zhang, H D; Ding, L; Weng, S X; Zhou, B; Ding, X T; Hu, L X; Qi, Y J; Yu, F Y; Feng, T J; Zhang, J T; Fang, P F; Zhang, S; et al.
Abstract: Background: A variety of supraventricular arrhythmias (SVAs) may occur in patients with hypertrophic cardiomyopathy (HCM). The characteristics and long-term ablation outcomes of different types of SVAs in HCM have not been comprehensively investigated. Methods: We retrospectively enrolled 101 consecutive symptomatic HCM patients with suspected arrhythmia from May 2010 to October 2020. The clinical features and ablation outcomes of patients with SVAs were further analyzed. Results: Seventy-eight patients had SVAs, consisting of 50 (64.1%) atrial fibrillation (AF), 16 (20.5%) atrial flutter (AFL), 15 (19.2%) atrioventricular reentrant tachycardia (AVRT), 11 (14.1%) atrial arrhythmia (AT), and 3 (3.8%) atrioventricular nodal reentrant tachycardia (AVNRT). Thirty-four patients underwent catheter ablation including 14 for AF, 9 for AVRT, 6 for AFL, 3 for AVNRT, 1 for both AF and AFL, and 1 for both AF and AVRT. They were followed up for a median (interquartile range) of 58.5 (82.9) months. There were no recurrences for patients with non-AF SVAs. For patients with AF, the 1- and 7-year AF-free survival were 87.5% and 49.5%, respectively. A ROC analysis revealed that a greater left ventricular end-diastolic dimension (LVEDD) was associated with higher recurrence of AF with an optimum cutoff value of 47mm (c-statistic = 0.91, p=0.011, sensitivity = 1.00, specificity = 0.82). In Kaplan-Meier analysis, patients with LVEDD ≥47mm had worse AF-free survival (log-rank p=0.014). Conclusions: AF is the most common SVA in HCM, with AFL, AVRT, AT, and AVNRT ranking the second to the last according to the prevalence. The long-term catheter ablation outcome for non-AF SVAs in HCM is satisfying. A greater LVEDD predicts AF recurrence after catheter ablation in patients with HCM. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): National Natural Science Foundation of China